(untitled) (Journal of Economic Research & Business Administration, 2018)
This article deals with the revision of the main targets of monetary policy. Monetary instruments of regulation become main factors that influence on the economic entities and ensure conditions for their investment and economic activity. Central banks, being responsible for monetary policy, provide daily struggle against inflation, market volatility and financial system’s instability. Central banks in their activity choose main priorities of the monetary policy aiming to establish a price stability, an effective level of money supply and circulation, payment system development etc. High level of inflation in Kazakhstan; weakness of tenge; exchange rates’ unpredictable behavior; price volatility of financial instruments on the internal market; instability of local banking system; as well as business units and households suffering from “expensiveness” of money – evidence about deep problems in financial system and on money market. Stated problems specify the relevance of the research and determines scientific interest to monetary policy in Kazakhstan and in foreign countries. Main purpose of the research is to clarify core principles of monetary policy and adopt them to the needs of national economy.